The Effectiveness of Character Values–Based Psychodrama Techniques in Enhancing Emotional Intelligence Among Public Junior High School Students in Ternate City - Rahmifanti R. Jacub; Diana Septi Purnama (Eduvest - Journal of Universal Studies, 2026)
This study emphasizes the importance of emotional management among junior high school students, particularly during adolescence—a developmental phase marked by significant emotional changes. Emotional intelligence is crucial for students’ social adaptation, communication, and academic success. To address the emotional and social challenges faced by students, this research applies psychodrama techniques as a group guidance method to help develop students’ emotional intelligence. The study employed a quantitative approach using a nonequivalent control group experimental design. The sample consisted of 16 students from SMP Negeri 1 Kota Ternate and SMP Negeri 7 Kota Ternate, selected through purposive sampling based on low levels of emotional intelligence. The participants were divided into two groups: an experimental group that received group guidance using psychodrama techniques and a control group that did not receive the intervention. Data were collected using an emotional intelligence scale with Cronbach’s alpha reliability coefficient of 0.762. Measurements were conducted before and after the intervention, and data analysis used the N-gain score to assess changes in emotional intelligence. The results showed a significant improvement in the emotional intelligence of students in the experimental group, with an N-gain score of 0.75, indicating a high level of effectiveness. These findings demonstrate that psychodrama is an effective technique for enhancing students’ emotional intelligence, helping them better understand emotions, build empathy, and develop interpersonal skills. This study contributes valuable insights into school guidance practices and supports the use of psychodrama as an innovative method to foster students’ emotional, social, and academic development.